Acoustic disruption system - Li, Hanyu (Nanyang Technological University, 2024)
Speech Jammer is a type of non-lethal acoustic hailing device used for directional acoustic air transmission to disrupt speeches made in public. There has been a growing interest in its application in military, law enforcement and homeland security scenarios. The project aims to create a Speech Jammer system using SensComp Series 600 Electrostatic Ultrasonic Transducers. The utilization of such component allows for higher frequency response, wider frequency bandwidth and longer working range than other similar products. The objective of this report is to refine the design of expandable EUT array housing module for the Speech Jammer system, and to construct a 1:1 scale mockup to support future testing of the electronic components. The mockup is constructed using polylactide (PLA) material via FDM 3D printing technology. Detail drawings of EUT housing is included and a 3x2 module is built to examine the feasibility of expanding into larger arrays. Unfortunately, the performance of the prototype 3D printed EUT housing was unable to be tested due to lack of suitable testing equipment and must be carried out by future project teams.